Desempenho de vocabulário em crianças pré-escolares institucionalizadas - Misquiatti, Andréa Regina Nunes; Nakaguma, Patrícia Gondo; Brito, Maria Cláudia; Olivati, Ana Gabriela (ABRAMO Associação Brasileira de Motricidade Orofacial, 2015)
PURPOSE: to evaluate the vocabulary performance of institutionalized children and compare it with the performance of children which belong to public and private schools. METHODS: 16 children at institutional care in shelter, of both genders, aged between 4 and 5 years and 11 months (experimental group) participated. As the control group, 32 children from public (n=16) and private (n=16) schools matched for age participated, totaling 48 participants. A Vocabulary Test (ABFW) was used, to evaluate the performance of the vocabulary. This test verifies the child's lexical competence and the resources of significance used to name the target word. Statistical analysis of data was performed to analyze differences between the surveyed groups (Kruskal-Wallis). RESULTS: it was possible to observe that institutionalized children showed lower performance in the vocabulary test in relation to the control groups, which showed no differences between them. In addition, all children showed more difficulty in the semantic fields professions and places. CONCLUSION: children in situations of institutional care have underperformed vocabulary for their age and inferior than the performance of preschool children in public and private schools who reside with their families.

OBJETIVO: verificar o desempenho de vocabulário de crianças institucionalizadas e comparar com o desempenho de crianças pertencentes à rede pública e particular de ensino. MÉTODOS: participaram deste estudo 16 crianças em situação de acolhimento institucional em abrigo, de ambos os gêneros, com idades entre 4 anos a 5 anos e 11 meses (grupo experimental). Para compor o grupo controle, participaram 32 crianças provenientes de escolas pública (n=16) e privada (n=16) pareadas por idade, totalizando 48 participantes. Para a verificação do desempenho de vocabulário foi utilizado o Teste de Vocabulário - ABFW que verifica a competência lexical da criança e os recursos de significação utilizados para nomear a palavra alvo. Foi realizada a análise estatística dos dados a fim de analisar diferenças entre os grupos pesquisados (Teste de Kruskal-Wallis). RESULTADOS: foi possível observar que as crianças institucionalizadas demonstraram desempenho inferior na prova de vocabulário em relação aos grupos controle, que não apresentaram grandes diferenças entre si. Cabe mencionar que todas as crianças demonstraram maior dificuldade nos campos conceituais profissões e locais. CONCLUSÃO: crianças em situação de acolhimento institucional em abrigo possuem desempenho vocabulário abaixo do esperado para a idade e inferior ao desempenho de pré-escolares de escolas pública e privada que residem com suas famílias.
Vocabulary performance in institutionalized preschool children
Keywords: Vocabulary; Child Language; Child, Institutionalized; Speech, Language and Hearing Sciences; Vocabulário; Linguagem Infantil; Criança Institucionalizada; Fonoaudiologia